The acceptability, feasibility, and preliminary efficacy of a supported online self-help treatment program for binge-eating disorder - Rom, Sean; Miskovic-Wheatley, Jane; Barakat, Sarah; Aouad, Phillip; Kim, Marcellinus; Fuller-Tyszkiewicz, Matthew; Maguire, Sarah (Frontiers in Psychiatry, 2023)
Introduction: Studies in transdiagnostic eating disorder (ED) samples suggest supported online selfhelp programs (eTherapies) are effective and may improve access to treatment; however, their evaluation in those with binge-eating disorder (BED) is limited. Given BED's high prevalence and low levels of treatment uptake, further eTherapy evaluation is needed to broaden access to effective, evidence-based treatment options. The aim of this study was to investigate the acceptability, feasibility, and preliminary efficacy of a supported eTherapy for those with BED or subthreshold BED, and to examine symptom change across the duration of therapy. Method: Nineteen women with BED completed a supported, 10-session Cognitive Behavioural Therapy-based eTherapy in an uncontrolled, pre-post, and three month follow up intervention study. Key outcomes were assessed by the Eating Disorder Examination Questionnaire (EDE-Q): objective binge episode (OBE) frequency and ED psychopathology. Feasibility was evaluated via program adherence and dropout, whilst acceptability was assessed through participant feedback posttreatment. Weekly symptom change (ED psychopathology) during treatment was assessed by the Eating Disorder Examination -Questionnaire Short (EDE-QS). This is a provisional file, not the final typeset article Results: Generalised estimating equations showed statistically and clinically significant reductions in OBEs and ED psychopathology (large effects) post-treatment, with these decreases maintained at follow up. Across weekly assessment, a marked slowing in the rate of change in ED psychopathology was observed after four sessions of the program. Program feasibility was high (i.e., 84% of content completed), as was program acceptability (i.e., 93% of participants expressed high levels of satisfaction). Discussion: These results support the acceptability, feasibility, and preliminary efficacy of a supported eTherapy program for those with BED and suggest the variability of symptom change across the duration of therapy. Future research should further investigate findings in an adequately powered randomised controlled trial.